PENGARUH LATIHAN FORWARD AND BACKWARD SIDE SHUFFLE MINIHURDLE DRILL TERHADAP KELINCAHAN PEMAIN SEPAKBOLA SSB YAPORA FRATAMA U-13 - Pramika, Nolly Octa Pramika Octa Pramika; Wijayanti, Ni Putu Nita Wijayanti Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The issues raised in this study is " What is the effect of exercise forward and backward side shuffle minihurdle drill toward agility at the football players Yapora Fratama U-13 Football School Athlete.?" This research is experimental research that aims to find out the effect of exercise forward and backward side shuffle minihurdle drill toward agility at the footbal players Yapora Fratama U-13 Football School Athlete. The population this eksperimen all football players Yapora Fratama Football School Athlete. This study used Purposive sampling at the specific Under thirteen years old. Were obtained and collected through the initial test and final test before and after forward and backward side shuffle minihurdle drill using a meansuring tool that is illinois agility run test. The method of processing data using descriptive statistics calculations and to test the hypothesis using the t test. The hypothesis proposed in this study is the effect of exercise forward and backward side shuffle minihurdle drill to the agility at football players Yapora Fratama U-13 Football School Athlete. The results of the t test produced 6,18 and 1,771 ttable at the significant level of 0.05. Means > t table. It can be concluded that Ha can be Received.This gives the conclusion that there is a significant effect of exercise forward and backward side shuffle minihurdle drill to the agility in men's soccer team football players Yapora Fratama U-13 Football School Athlete. Key Words:  Exercise forward and backward side shuffle minihurdle drill. Agility